2016
DOI: 10.1093/nar/gkw1293
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase 3β is the major topoisomerase for mRNAs and linked to neurodevelopment and mental dysfunction

Abstract: Human cells contain five topoisomerases in the nucleus and cytoplasm, but which one is the major topoisomerase for mRNAs is unclear. To date, Top3β is the only known topoisomerase that possesses RNA topoisomerase activity, binds mRNA translation machinery and interacts with an RNA-binding protein, FMRP, to promote synapse formation; and Top3β gene deletion has been linked to schizophrenia. Here, we show that Top3β is also the most abundant mRNA-binding topoisomerase in cells. Top3β, but not other topoisomerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 30 publications
(101 reference statements)
3
60
0
Order By: Relevance
“…Consistent with this, copy number variants and de novo mutations in TOP3B have been linked to an increased risk of neurodevelopmental and cognitive disorders, including autism and schizophrenia (68,(166)(167)(168)(169). The involvement of TOP3B in cognition is likely conserved across species because TOP3B has been shown to be essential for correct synaptic formation in both mice and flies (67,166). These phenotypes, also observed when TOP1 and TOP2B are defective, suggest that TOP3B has a role in releasing topological constraints associated with transcription (170).…”
Section: Roles Of Top3b In Rna Metabolismmentioning
confidence: 72%
See 1 more Smart Citation
“…Consistent with this, copy number variants and de novo mutations in TOP3B have been linked to an increased risk of neurodevelopmental and cognitive disorders, including autism and schizophrenia (68,(166)(167)(168)(169). The involvement of TOP3B in cognition is likely conserved across species because TOP3B has been shown to be essential for correct synaptic formation in both mice and flies (67,166). These phenotypes, also observed when TOP1 and TOP2B are defective, suggest that TOP3B has a role in releasing topological constraints associated with transcription (170).…”
Section: Roles Of Top3b In Rna Metabolismmentioning
confidence: 72%
“…Indeed, the TOP3B gene resides on chromosome 22q11.2 in the human genome, a region frequently affected by deletions or duplications leading to congenital heart disease, facial malformation and cognitive dysfunction (68,(161)(162)(163)(164)(165). Consistent with this, copy number variants and de novo mutations in TOP3B have been linked to an increased risk of neurodevelopmental and cognitive disorders, including autism and schizophrenia (68,(166)(167)(168)(169). The involvement of TOP3B in cognition is likely conserved across species because TOP3B has been shown to be essential for correct synaptic formation in both mice and flies (67,166).…”
Section: Roles Of Top3b In Rna Metabolismmentioning
confidence: 89%
“…and Top3b have been linked to autism 106,156,207,[227][228][229][230] . Top3b has topoisomerase activity on both DNA and RNA 207,228 and is the major RNA topoisomerase for mRNAs 231 . Significantly, independent labs have found that Top3b is in a complex with a tudor-domain protein, Tdrd3, and FMRP 207,228,232 .…”
Section: A Seventh Common Upstream Regulatory Pathway Dmd (Dystrophimentioning
confidence: 99%
“…Human TOP3B remained remarkably understudied until the recent discovery that it can act as a Type IA topoisomerase for both DNA and RNA (Ahmad et al, 2017a;Ahmad et al, 2017b;Ahmad et al, 2016;Stoll et al, 2013;Xu et al, 2013). Although TOP3B is not essential in flies or mice, Top3B knockout mice develop autoimmunity (Kwan et al, 2007), infertility (Kwan et al, 2003), have reduced lifespan (Kwan and Wang, 2001), abnormal neurodevelopment and defective synapse formation (Ahmad et al, 2017a;Ahmad et al, 2017b;Xu et al, 2013). In humans, TOP3B genomic deletion has been linked with Schizophrenia in a Northern Finnish subpopulation (Stoll et al, 2013).…”
Section: Introductionmentioning
confidence: 99%